Incidence of childhood leukemia and lymphoma in India - Smita Asthana; Satyanarayana Labani; Swati Mehrana; Sameer Bakhshi (Elsevier, 2018)
Background: Leukemia and lymphoma are the most prevalent cancers globally among children. Objective: To provide an updated review on incidence of childhood leukemia and lymphoma incidence from Population Based Cancer Registries (PBCRs) in India. Methods: Data obtained on cancers in childhood for either sex in age groups of 0-14 years from National Cancer Registry Programme Reports (NCRP).The indicators of age-specific rate (ASpR), age-adjusted-rate (AAR) per million (pm) and number of incident cases for leukemia and lymphomas were noted for the years 2012-2014. The summarization of 24 PBCRs data was compiled in six regions of India. Results: Ratio of female to male cases ranged from 1: 0.9 to 1:5.6 for leukemia and 1:1.0 to 1:4.1 for lymphoma. For boys, AAR ranged from 0.0 pm/year (North East) to 101.4 pm/year (North). For girl's incidence ranged from 0.0 pm/year in West and North East to 62.3 pm/year in North region of India. For boys Age Specific Rate (ASpR) pm for all leukemia type was ranged from 0.0 to 9.9 among under five years while in case of girls ASpR pm for all leukemia ranged from 0.0 to 6.4 among 5-9 years of age. ASpR for all types of lymphoma ranged from 0.0 to 3.2 in boys among 5-9 years of age while in girls the range was from 0.0 to 1.5 among 10-14 years of age. Conclusion: Lymphoma and leukemia cases were maximum in North region of India. Male preponderance of leukemia and lymphoma in the Indian setting could be multifactorial including possible gender bias as well as disease biology. Keywords: Childhood cancer incidence, Lymphoma, Leukemia, India